Uterine smooth muscle tumor of uncertain malignant potential: A rare cause of multiple pulmonary nodules - Kotsopoulos, Ioannis C; Barbetakis, Nikolaos; Asteriou, Christos G; Voutsas, Markos (Indian Journal of Medical and Paediatric Oncology, 2012)
Smooth muscle tumors of uncertain malignant potential (STUMP) are mesenchymal uterine tumors lying between benign leiomyomas and leiomyosarcomas. Although lung metastases from uterine leiomyosarcoma are common, ′′STUMP′′ usually does not metastasize. A case of a 51-year-old woman with progressive dyspnea on exertion and multiple space-occupying lesions in both lungs is presented. She had a history of a total abdominal hysterectomy 3 years ago. Lung biopsy through video-assisted thoracic surgery was consistent with metastatic malignant smooth muscle cell tumor. She received multiple cycles of chemotherapy and died 11 months later. Cell necrosis, atypia and mitotic count are important criteria determining the malignant potential of a uterine smooth muscle tumor. The diagnosis and clinical course of STUMP are not totally and clearly known, and metastasis, especially pulmonary with pleural effusion, is not a common phenomenon. When this occurs, prognosis seems to be poor. Surveillance of these patients should be close and long term.
Keywords: Leiomyoma; leiomyosarcoma; lung; metastasis; uterus